Predictors of emotional intelligence amongst university students - Cronje, Johrine (University of the Free State, 2019)
The education of the labour force directly impacts the economy of a country. The successful employment of university students indicates a strong positive relationship with regards to students’ academic performance and emotional well-being, especially during their university years. University students experience several psychological challenges that often lead to a withdrawal from their studies. Various studies within South Africa identified psychological challenges, such as depression, anxiety and post-traumatic stress, which leave students feeling despondent and vulnerable, often resulting in academic failure. Almost 50% of students complete their three-year or four-year undergraduate degree within five years. These statistics raise a concern to South Africa’s competent labour market. The emotional intelligence of undergraduate university students is thus an important matter of concern, as it seems to be on the decrease, due to the technogenic age. These students’ attention is held captive by technology use, resulting in fewer opportunities to practice emotional competencies as they find safety in the digital space rather than face-to-face interactions. However, resilience enables undergraduate university students to persevere through turbulent times. Students with a high level of resilience are better capable to alter or sustain their emotional reactions to the demands of the constantly changing emotional environment. This ability has a strong positive correlation with emotional intelligence and a positive effect on the mental health of undergraduate university students. This study aims to investigate which variables or combination of variables explain a significant percentage in emotional intelligence amongst undergraduate university students. In order to determine the relationship between variables, a correlational design was central to the non-experimental, quantitative study. A non-probability convenience sampling method was employed to recruit 1191 registered undergraduate university students between the ages of 18 and 30 at the University of the Free State. The sample included participants from all ethnic groups, cultures, languages, genders, provinces, majors and religious backgrounds. The measuring instruments included a biographical questionnaire, The Schutte Emotional Intelligence Questionnaire, the Resilience Scale and the Media and Technology Usage and Attitudes Scale. A hierarchical multiple regression analysis was used to analyse the data. The combination of the predictor variables (Resilience, Media and Technology usage, Age, Gender, Religious Affiliation and Religious Practice) statistically and practically significantly predicted emotional intelligence. The results further indicated that resilience is the only predictor variable with a statistically significant contribution to the emotional intelligence of undergraduate university students with a large corresponding effect size (f2 = 0.48). It was found that resilience accounted for 27.8% variance in the Emotional Intelligence scores of the undergraduate university students. This finding concurs with the building blocks of the model of emotional intelligence competencies (Mayer et al., 2000). It is suggested that resilient individuals are able to (1) recognise emotions, (2) use emotions to facilitate thought, (3) make sense of emotional information and (4) regulate their emotions (Mayer, Salovey, & Caruso, 2000; Schutte, Malouff, & Thorsteinsson, 2013).
Dissertation (M.A.(Psychology))--University of the Free State, 2019
Keywords: Age; Emotional intelligence; Free State; Gender; Religious affiliation; Religious practice; Resilience; Media and technology usage; Undergraduate university students